(untitled) (Journal of Enam Medical College, 2012)
A 42-years old lady reported with slowly progressive reddish lesions over the nose, followed by atrophy and ulceration for about 6 years. Clinical examination revealed atrophied, ulcerated, erythematous lesions over central face, forehead and neck destroying whole nose. Mantoux test resulted 16×18 mm on 48 hours observation. Histopathological examination of the lesion showed noncaseating grunuloma along with Langhans giant cells in the upper dermis surrounded by lymphocytes. The conclusive diagnosis was lupus vulgaris based on above findings. Six months therapy with INH 300 mg plus rifampicin 600 mg supplemented by initial 2 months ethambutol 1000 mg plus pyrazinamide 1500 mg daily resulted clean-looking perforation with healthy margin. DOI: http://dx.doi.org/10.3329/jemc.v1i1.11140 J Enam Med Col 2011; 1(1): 43-45